Computational Methods to Study the Structure and Dynamics of Biomolecules and Biomolecular Processes From Bioinformatics to Molecular Quantum Mechanics - Liwo, Adam (Springer Series on Bio- and Neurosystems, 2019)
This book provides a comprehensive overview of modern computer-based techniques for analyzing the structure, properties and dynamics of biomolecules and biomolecular processes. It is organized in four main parts; the first one deals with methodology of molecular simulations; the second one with applications of molecular simulations; the third one introduces bioinformatics methods and the use of experimental information in molecular simulations; the last part reports on selected applications of molecular quantum mechanics. This second edition has been thoroughly revised and updated to include the latest progresses made in the respective field of research.